SARS-CoV-2 seroprevalence in a cohort of asymptomatic, RT-PCR negative Croatian first league football players - Vince, A.; Zadro, R.; Šostar, Z.; Ljubin Sternak, S.; Vraneš, J.; Škaro, V.; Projic, P.; Molnar, V.; Matišic, V.; Baršic, B.; Lauc, G.; Lovric-Makaric, Z.; et al. (Journal of Pharmacy and Pharmacology Research, 2020)
Background: During the COVID-19 pandemic the Croatian Football Federation has launched a new model of pre-season systematic examination of football players, emphasizing the diagnosis of asymptomatic SARS-CoV-2 infection and preventing further spread among the players.